Correlated color temperature preferred by observers for illumination of artistic paintings - Pinto, Paulo Filipe Salgado (2008)
The visual effects of lighting on art paintings is an important aspect that should be considered by museum curators. The aim of this work was to determine the correlated color temperature (CCT) of daylight illumination preferred by observers when appreciating art paintings. Hyperspectral images of 11 oil paintings were collected at the museum, and the appearance of the paintings under daylight illuminants with CCT from 25,000 K to 3600 K was computed. In a psychophysical experiment using precise CRT reproductions of the paintings, observers had to adjust the CCT of the illuminant such that it produced the best visual impression. It was found that the distribution of observers' preferences had a maximum at a CCT of about 5100 K and that this value did not depend on whether the observers were undergraduate students or museum visitors or on the degree of adaptation to the color of the illumination. These results suggest that observers prefer a more bluishwhite light than that normally used in museums. © 2008 Optical Society of America.